A autonomia da vontade e o problema da fundamentação da moralidade no pensamento de Immanuel Kant - Costa, Rafaella Silveira Sucupira da (2019)
In this Dissertation dealing with the problem of the foundation of morality in the thought of Immanuel Kant. More specifically, we aim to understand the possibility of the autonomy of the will as the supreme principle of Kantian morality. The interest in this theme is justified by the relevance that it assumes for traditional moral philosophy. In our investigative journey, we have chosen three specific objectives, namely: to understand the practical role of reason, both in its instrumental aspects, as a means to achieve a definite end, and in its moral aspects, as a determinant faculty of moral action; to understand the problem of the foundation of morality, that is, to analyze the illegitimate principles (of happiness and perfection) and the legitimate principle of morality (the autonomy of the will); and, finally, to highlight the problem of the realization of moral actions in the phenomenal world. With this, we intend to analyze the contours, limits and repercussions of the Kantian moral philosophy and, furthermore, how the problem of the foundation of morality seems still current in the scope of the contemporary ethics and the criticisms that are sent to him by some authors.